Legal Analysis of Accountability and Transparency in the Distribution of Waqf Management Returns - Sholihah, Fithriyatus; Heradhyaksa, Bagas (Jurnal Hadratul Madaniyah, 2025)
This article examines the compatibility between Article 23 of the Indonesian Waqf Board (BWI) Regulation No. 01 of 2020 on the distribution of waqf proceeds and the Financial Accounting Standards (PSAK) 112 on Waqf Accounting. Article 23 stipulates that net proceeds shall be allocated with a maximum of 10% for Nazhir, at least 50% for the Mauquf ‘Alaih, and the remainder for reserves. However, the regulation does not specify the accounting basis for calculating and reporting such net proceeds. In contrast, PSAK 112 provides a comprehensive framework for recognition, measurement, presentation, and disclosure of waqf assets, including the separation between waqf and non-waqf assets, as well as the preparation of statements of financial position, activities, cash flows, and notes. This study employs a normative juridical method with statutory, conceptual, and comparative approaches, supported by international literature on accountability in waqf management. The findings reveal a regulatory gap between BWI Regulation and PSAK 112, which risks undermining transparency and accountability. The study recommends regulatory harmonization with PSAK 112, capacity building for Nazhir in financial reporting, and the adoption of digital reporting systems based on standardized accounting practices to strengthen public trust and ensure sustainable waqf governance.